Penggunaan peta konsep untuk meningkatkan pencapaian mata pelajaran sejarah bagi pelajar tingkatan dua - Zahara Aziz,; Nurliah Jair, (penerbit ukm, 2009)
The purpose of this research was to examine the usage of concept map in increasing students performance to increase students’ performance for history subject in Form 2. Besides that, this research also examined whether using concept map would increase students performance. Futhermore, this research also studied students acceptance towards concept map. This research was done in a school in Cheras, Selangor. Action research design employing the qualitative and quantitative methods with the research sample used was 37 students and one teacher from a school in Cheras. This research used concept map as a dependent variable and academic achievement as independent variable. The research used sets of multiple choice tests as the pretest and post test questionnaires to view students’ acceptance towards concept map, teacher’s observation form, lesson plan and also interviews between teacher and students. The analyzed data used was inferential and descriptive statistic. The research result showed that there was no significant difference in the means of achievement between genders in the pre and post-test. Meanwhile, there was a significant difference in the mean achievement of the pre-test and post-test. The students’ acceptance towards concept map was positive-medium. Overall, concept map was efficient in increasing students’ performance in history subject.